Performance of Porous Asphalt Mixture Using HDPE (High Density Polyethylene) Plastic Additives - Sa'dillah, M.; Oktaviastuti, Blima; Pandulu, Galih Damar; Arifianto, Andy Kristafi; Ndima, Susana Rambu (Jurnal Fondasi, 2024)
Efforts are being made to increase the strength or stability of porous asphalt mixtures by adding HDPE plastic waste. The reason for making HDPE plastic added material is that it has the same properties as asphalt, namely thermoplastic has a penetration value equivalent to pen 60/70 asphalt. This study aims to: (1) Describe the characteristics of the constituent materials of porous asphalt mixtures and (2) The effect of adding HDPE plastic to porous asphalt mixtures was reviewed based on the Marshall Test, Cantabro Loss, and Asphalt Flow Down. The research method uses experimental research in the laboratory. The research will be carried out using the Australian Asphalt Pavement Association (AAPA) 2004 approach. The research was carried out with pen 60/70 asphalt content, namely 4%, 4.5%, 5%, 5.5%, and 6% to find the value of asphalt content. optimum, then will be added with a ratio of HDPE material 0%, 2%, 4%, 6% and 8% to the total weight of KAO. The results of the Marshall characteristic analysis for porous asphalt mixtures with varying levels of 2% HDPE have met the specifications on the grounds that all parameters have met the requirements of the Australian Asphalt Pavement Association (AAPA 2004) with a VIM value at 2% content of 18.18%, for a VMA value of 29.40%, while the stability value is 640 kg and the flow value obtained is 2.30 mm while the MQ value is 284.63 kg/mm.